Pengaruh Profitabilitas Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Intervening Pada Perusahaan Properti Dan Real Estate Yang Terdaftar Di Bursa Efek Indonesia 2020-2024 - Viola Sisi Vanilia (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to examine the effect of profitability and firm size on firm value with capital structure as an intervening variable in property and real estate companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This research uses a quantitative approach with secondary data derived from annual financial statements. The sample was selected using purposive sampling, resulting in 22 companies observed over five years. Data analysis was conducted using multiple linear regression and path analysis with SPSS version 26. The results indicate that profitability has a negative and significant effect on capital structure, while firm size has a positive and significant effect on capital structure. However, profitability, firm size, and capital structure do not have a significant effect on firm value. Furthermore, capital structure does not mediate the relationship between profitability and firm value, nor between firm size and firm value. These findings suggest that capital structure decisions have not been a determining factor in increasing firm value in the property and real estate sector during the research period.